2015
DOI: 10.3389/fmicb.2015.00179
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities in dark oligotrophic volcanic ice cave ecosystems of Mt. Erebus, Antarctica

Abstract: The Earth's crust hosts a subsurface, dark, and oligotrophic biosphere that is poorly understood in terms of the energy supporting its biomass production and impact on food webs at the Earth's surface. Dark oligotrophic volcanic ecosystems (DOVEs) are good environments for investigations of life in the absence of sunlight as they are poor in organics, rich in chemical reactants and well known for chemical exchange with Earth's surface systems. Ice caves near the summit of Mt. Erebus (Antarctica) offer DOVEs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 52 publications
1
83
1
Order By: Relevance
“…More recent work has described the composition of microbial communities in caves near the Mt. Erebus summit using a clone library (Tebo et al 2015) and in hot soils on Tramway Ridge using 454 sequencing (Herbold et al 2014). A reanalysis of the data from Herbold et al (2014) using the methods described here identified a large number of Cyanobacteria (5.3 % of total reads) belonging to the genera Plectolyngbya, Scytonema, and Fischerella.…”
Section: Discussionmentioning
confidence: 94%
“…More recent work has described the composition of microbial communities in caves near the Mt. Erebus summit using a clone library (Tebo et al 2015) and in hot soils on Tramway Ridge using 454 sequencing (Herbold et al 2014). A reanalysis of the data from Herbold et al (2014) using the methods described here identified a large number of Cyanobacteria (5.3 % of total reads) belonging to the genera Plectolyngbya, Scytonema, and Fischerella.…”
Section: Discussionmentioning
confidence: 94%
“…Such adaptations are important for microorganisms living on rock surfaces, which are often depleted in organic carbon, fixed nitrogen and biologically available phosphorus (Wainwright et al ., ; Barton et al ., ). Photoautotrophs inhabiting rocks exposed to sunlight can provide a source of fixed carbon to the wider microbial community, but environments that are largely isolated from photosynthetic carbon, such as marine sediments (Lever et al ., ) and caves (Barton et al ., ; Tebo et al ., ), are more usually colonized by oligotrophic and chemoautotrophic communities. Previous studies have suggested that the enhanced adhesion of cells to nutrient‐rich surfaces in marine sediments and the subsequent establishment of biofilms are important adaptations for microorganisms that would otherwise be starving in oligotrophic waters (Marshall, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of what is known regarding bacterial RubisCO function is derived from pure culture analyses and relatively few model enzymes. However, recent massive deoxyribonucleic acid (DNA) sequencing efforts have shown the abundant presence of diverse and novel RubisCO‐encoding genes in environmental communities of largely uncultivated bacteria and new candidate phyla, the so‐called ‘microbial dark matter’ (Wrighton et al ., 2012; submitted; Campbell et al ., ; Guo et al ., ; Castelle et al ., ; Tebo et al ., ). Although the physiological significance of these novel RubisCO enzymes is unquantified, these organisms likely have evolved significant structural and functional adaptations to allow CO 2 to be metabolized in diverse environments such as in marine surface waters, hydrothermal vents and the terrestrial subsurface (Witte et al ., ; Wrighton et al ., 2012; submitted; Böhnke and Perner, ; Castelle et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing, cloning and activity screening of purified recombinant proteins is possible on a small scale (Böhnke and Perner, 2015). However, it is not always possible to discern physiological function by sequence-gazing alone, nor is it practical to produce and individually screen and characterize recombinant proteins from the large number of novel RubisCO-encoding genes recently observed (Wrighton et al, 2012;submitted;Campbell et al, 2013;Guo et al, 2013;Castelle et al, 2015;Tebo et al, 2015). Whereas a previous study demonstrated the feasibility of studying environmentally derived RubisCO genes in a recombinant photosynthetic host (Witte et al, 2010), a directed functional metagenomic selection approach is necessary for highthroughput retrieval of desirable new RubisCO enzymes from uncultivated organisms.…”
Section: Introductionmentioning
confidence: 99%